2021
DOI: 10.5173/ceju.2021.285.3
|View full text |Cite
|
Sign up to set email alerts
|

Native tissue repair of cardinal/uterosacral ligaments cures overactive bladder and prolapse, but only in pre-menopausal women

Abstract: Introduction The aim of this article was to study the effect of native tissue cardinal/uterosacral ligament repair on overactive bladder (OAB) and pelvic organ prolapse (POP). Material and methods Inclusion criteria included decrease of urge symptoms following insertion of a gauze tampon in the posterior fornix of vagina (‘simulated operation’). Exclusion criteria included SUI, POP grades 3–4. The surgery consisted of plication of cardinal/uterosacral ligaments. Post-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 25 publications
(34 reference statements)
0
33
0
Order By: Relevance
“…Since about 2011, any mesh products other than for stress urinary incontinence became progressively banned in many countries world-wide. Native USL repair is a good option but only for premenopausal women ( 17 ). In a comparative study, Shkarupa et al demonstrated high cure rates for overactive bladder (OAB) symptoms and prolapse in premenopausal women, but gave catastrophically low results in post-menopausal women, probably because of collagen breakdown in ligaments after the menopause ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since about 2011, any mesh products other than for stress urinary incontinence became progressively banned in many countries world-wide. Native USL repair is a good option but only for premenopausal women ( 17 ). In a comparative study, Shkarupa et al demonstrated high cure rates for overactive bladder (OAB) symptoms and prolapse in premenopausal women, but gave catastrophically low results in post-menopausal women, probably because of collagen breakdown in ligaments after the menopause ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shkarupa et al ( 9 ) successfully used a gauze roll inserted during the day and overnight to test eligibility of patients with OAB symptoms for CL/USL plication ( 9 ) (see Appendix 5 for further references which surgically validate the predictive value of the diagnostic system).…”
Section: Part IV Of the Flow Chart—simulated Operationsmentioning
confidence: 99%
“…Traditionally, women with prolapse are treated with native tissue repair which reconstructs the vagina and/or supporting ligaments by native tissue repair. In a comparative study, Shkarupa et al achieved high cure rates for prolapse and overactive bladder (OAB) symptoms by cardinal and USL repair at 18 months, but only in premenopausal women ( 3 ); there was a catastrophic drop in cure rates for both symptoms and prolapse in postmenopausal women at 18 months ( Table 1 ). Based on their department’s data, Shkarupa et al recommended polypropylene slings for postmenopausal women who had surgery for prolapse and/or symptoms.…”
Section: Collagenmentioning
confidence: 99%